Enterprising instructional initiative: development of a human resource management major in the Middle East. (10th March 2015) - Fusilier, Marcelline; Russell, John D.; Aljamal, Ali
Enterprising higher education management with a focus on instructional innovation may help teaching universities as they confront the dynamism of the transnational higher education market. The present study is documentation of an enterprising process for instructional innovation at the American University of Kuwait. Information from the employment market was used to identify an apparent opportunity to offer a human resource management (HR) undergraduate major. Stakeholder engagement and benchmarking for shaping the programme are illustrated as well as efforts to establish a reputation for quality. Freire's theory of conscientisation was applied to structure learning in the coursework of the new programme. Critical factors enabling the enterprising initiative included use of business concepts in university management, programme validation from reputable external agents and stakeholder input.